Direct Medical Costs of Kidney Stone: A Retrospective Study - Trung Quang Vo; Tram Thuy Ngoc Nguyen; Thao Quy Thi Le; Luyen Dinh Pham; Quang Vinh Tran (Journal of Clinical and Diagnostic Research, 2018)
Introduction: Nephrolithiasis imposes a weighty economic burden on individuals and their families, the healthcare system, and society. In Vietnam, expenses related to nephrolithiasis are poorly investigated. Aim: To assess the direct medical cost of treating nephrolithiasis and provide data on the economic burden of kidney stone disease in actual clinical practice in Vietnam. Materials and Methods: A retrospective costs approach from a hospital perspective was employed. Data was collected from Binh-Dan Hospital – a public hospital in Ho Chi Minh City, Vietnam, to estimate direct medical costs. The Bootstraping method of 2,000 times of resampling was used due to a skewed data. Results: A total of 57,332 nephrolithiasis patients from BinhDan Hospital were enrolled in the study. Throughout the study period, the per-episode direct medical cost of nephrolithiasis in the Inpatient Department (IPD) and outpatient department (OPD) was US$ 532.1 (95% CI, 524.8-539.9) and US$ 50.1 (95% CI, 49.7-50.4), respectively. The two most significant components of direct medical cost were medical procedures (24.7%) and pharmaceuticals (20.2%). Conclusion: The findings indicate that nephrolithiasis places a considerable economic burden on public healthcare services in Vietnam. Analysis demonstrating the magnitude of the economic impact of nephrolithiasis management in Vietnam’s healthcare system may help facilitate health and social policy interventions to improve the prevention and treatment of nephrolithiasis.